The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1155/2015/196280
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Research Directions in Cognitive Sensor Networks for Elderly Housing Design

Abstract: As part of resolving the issue related to super-aging society, various information systems for the elderly care have been developed utilizing cognitive sensor networks. However, many sensor network-based systems cognizing radios, resources, environments, and so forth are not practically feasible and useful for the elderly themselves. Therefore, this paper tries to propose novel research directions for designing smart residential environment for the elderly in terms of converging information technologies includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Although the basis for smart homes is technology and computer science, research on the environment for older adults is essential as it is directly related to the quality of life. As Suh et al (2015) mentioned, “studies on residential environment for the elderly have not actively been conducted so far” [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the basis for smart homes is technology and computer science, research on the environment for older adults is essential as it is directly related to the quality of life. As Suh et al (2015) mentioned, “studies on residential environment for the elderly have not actively been conducted so far” [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Layton and Steel (2019) suggested that a smart home design should consider built environment, interfaces, and their interaction with residents (disabled and older adults) from an integrated perspective [ 79 ]. Suh et al (2015) presented convergence research of cognitive information technologies in terms of cognitive sensor networks and architectural design for the elderly [ 77 ]. Appropriate funding will facilitate such convergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of CR sensor networks (CRSNs) was described by Suh et al 19 and Kaur et al 20 Several information systems for elderly care have been developed using cognitive sensor networks to address the dilemma of a super-aging society. However, many sensor-network-based systems that monitor radios, resources, habitats, and other factors are not practical or useful for the elderly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu, W. Gabran, P. Pawelczak, and D. Cabric [12] present a mathematical analysis of the accuracy of estimating PU's mean duty cycle u, as well as the mean off-and on-times, but the method considers the PU characteristics and sensing problem is not considered. To generalize this part almost similar methods are implemented in all references [13][14][15][16][17][18][19][20]. Nowadays, millions of sensors are entering the market and the world of sensor communication is getting more attention with its problems as explained in our previous work in Kedir et al [21].…”
Section: Related Workmentioning
confidence: 99%